CHARACTERIZATION AND PROPERTIES INVESTIGATION OF SINGLE ROW DEEP GROOVE BALL BEARING FAILURE - MOHD SAMSURI, MUHAMAD SHAZARIZUL HAZIQ (IRC, 2017)
A single row deep groove ball bearing is used as the specimen throughout this project. The bearing was obtained from Shell Refining Company along with its specifications and was reported to have failure by the company itself. The objectives of this project are to investigate the types and causes of failures of the damaged single row deep groove bearing, and comes out with the preventions of the failure. The bearing material is AISI 52100 high carbon, chromium of low steel alloy which was used for more than 2 months. The bearing life cycle is calculated based on the information gathered from the company and the manufacturer. The result obtained is 2 months, which indicates that fatigue failure might exist. Visual inspection was conducted to investigate the physical damage of the bearing. Pitting and wear can be observed clearly on the railway of bearing inner and outer ring. Microstructural analysis is done using Scanning Electron Microscope (SEM), where small pores and microcracks could be seen on the bearing subsurface. The X-Ray Fluorescence (XRF) result obtained was compared with the real element composition of the AISI 52100 bearing material. The bearing has no manufacturing defect in terms of element composition. The hardness test was conducted using Rockwell “C” scale and the average result obtained is 62.9 HRC. The value is compared to the hardness value of the standard material AISI 52100 which is 64. The difference of both values is only 1.75%, which indicates the bearing has no manufacturing defect in terms of mechanical properties. These failures are caused by poor lubrication. Therefore, it is advisable to change the type of lubricant with a higher kinematic viscosity in order to have a better lubrication with a longer life span.